Pyoderma Gangrenosum with Oral Involvement and Multidisciplinary Management - de Souza Camargo, Héric [UNESP] (2025)
Introduction: Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis often associated with inflammatory bowel disease. Case report: We present a case of PG affecting the oral mucosa in a 31-year-old female with ulcerative colitis, necessitating total colectomy due to aggressive lesion progression. Despite initial adalimumab treatment, the lesions persisted, prompting a multidisciplinary approach. Following surgical intervention, including total colectomy and microvascularized graft with a forearm flap, the patient remained recurrence-free during a seven-year follow-up. Conclusion: This case underscores the complexity of PG and highlights the efficacy of a comprehensive therapeutic approach, emphasizing the importance of individualized management strategies in severe cases.